Answer:
The given expression is factorized as [tex]4y^2 - 1 = 0 \implies (2y -1)(2y +1) = 0[/tex]
Step-by-step explanation:
Here, the given expression to factorize is: [tex]4y^2 - 1 = 0[/tex]
Now, using Algebraic Identity:
[tex]a^2 - b^2 = (a + b) (a-b)[/tex]
Now here let a = 2y , b = 1
⇒ [tex](a) ^2 = (2y)^2 = 2y \times 2y = 4y^2\\\implies 4y^2 = (2y)^2 [/tex]
So, The given expression is equivalent to:
[tex]4y^2 - 1 = 0 \implies (2y)^2 - (1)^2 = 0\\\implies (2y -1)(2y +1) = 0[/tex]
Hence the given expression is factorized as [tex]4y^2 - 1 = 0 \implies (2y -1)(2y +1) = 0[/tex]